Exploring male students’ perceptions in doing collaborative writing in an EFL writing course - Tjawan, Yoana Vincentia (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
Literature informs that writing collaboratively can help students to interact more in class, lower their anxiety about completing tasks alone, and raise their confidence. However, despite the benefits of collaborative writing, not all English as a Foreign Language (EFL) students enjoy writing in a group. This study aimed at exploring male university students’ perceptions of doing collaborative writing in their EFL online writing class using Google Docs. Data were collected through semi-structured interviews with ten male university students at a private university in Central Java, Indonesia. The analysis results of this study indicate that most of the students showed a positive perception of their collaborative writing activity, such as getting useful and immediate feedback, fostering exchange of knowledge, information, and experience, and getting the work done faster. This study is expected to offer some insights for EFL teachers to design more effective online collaborative writing activities in EFL writing classrooms, specifically in an Indonesian higher education context.